Diversidade de inimigos naturais em cafezais sombreados - Tomazella, Vitor Barrile (2016)
Coffee is very important for Brazilian agribusiness, Brazil is the largest producer and exporter of coffee with over 2.2 million hectares cultivated and an income of more than 600 million dollars. However, the production dynamics is greatly influenced by biotic and abiotic factors. The crop is attacked by various diseases and pests, but there are many natural enemies that perform biological control of both, with emphasis on Prorops nasuta (Hymenoptera: Bethylidae), a parasitoid of the coffee berry borer larvae and Protonectarina sylveirae (Hymenoptera: Vespidae), a wasp that feeds on larvae of leaf miner. Diversification of crops is an important tool to maintain these organisms in agriculture. One way of diversification is the utilization of trees for shading, which help in maintaining and increasing the diversity in the crop and brings improvements to the agroecosystem. Thus this study's goal is to evaluate the influence of some tree species for shading in diversity of parasitoid and wasps in conventional coffee. This study was conducted at Fazenda da Lagoa, in Santo Antonio do Amparo municipality, MG, in conventional coffee plantations shaded with different tree species, which are: Teak, Acacia, Cedar and Avocado planted in two different densities. For comparison purposes, a crop in full sun system was used as a control. The parasitoids collected were identified in families and separated into morphospecies; the wasps collected were identified to species, when not possible to identify, were separated in morphospecies within the genre. We collected 3172 parasitoid individuals belonging to nine superfamilies, 21 families and 263 morphospecies, and 632 individuals of 23 species of wasps. Regarding parasitoids, the Acacia treatment showed greater diversity (3.77) and for wasps, Avocado treatment (1.70) with the highest diversity. The lowest diversity was found in Cedar (0.74) for the wasps and Teak (3.19) for parasitoids. The higher diversity was found in plants with high availability of resources such as nectar, pollen and shelter. Diversification with tree species can bring significant gains to agroecosystem assisting in increasing diversity and maintenance of natural enemies, helping the conservation biological control.